The device engine protection from improper fuel - Ковтун, А.К.; Турчак, В.М. (Proceedings of National Aviation University (archive), 2009)
Engine defence device from not corresponding fuel type is presented. A new method of determination fuel type correspondence. Gasoline and diesel versions are described.